ESTIMATION OF THE WAVE PARAMETERS DESIGNED IN THE SAOMAI - BENDINH, VUNGTAU SEAWATERS - Mau, Le Dinh (Vietnam Journal of Marine Science and Technology, 2009)
This paper presents the calculated results of wave parameters for design and construction of the nearshore hydro-structures such as wave height, wave period, wave length,  longshore  current  speed  induced  by  breaker  in  the  Saomai-Bendinh,  Vungtau seawaters  corresponding  to  50  years  return  period.  Wind  data  were  taken  from  Vungtau Station (1987 - 2006), extreme wind speed was calculated by FT-I distribution function; wave parameters in the offshore region were calculated by deep water wave model - Dolphin; wave parameters  in  the  nearshore  region  were  calculated  by  SWAN  model.  The  studied  results showed that Saomai - Bendinh seawaters was strongest affected by wave action from SW and W directions, especially in the area of shoals around Tau Islands and Longson. Dinh River channel  was  less  affected  by  wave  action.  The  typhoon  No.  28  (11/1962)  was  strongest affected to study area which generated significant wave height of 1.0 to 2.0 m and 2.0 to 2.5 m in the area around and off Tau Islands respectively.